Dancing the Numinous: Sacred and Spiritual Techniques of Contemporary American Belly Dancers - Jeana Jorgensen (Journal of Ethnology and Folkloristics)
In this paper, I explore how contemporary American practitioners of belly dance (as Middle Eastern dance and its many varieties are often called in the English-speaking world) conceptualize not only the spiritual dimensions of their dance, but also how the very notion of performance affects sacred and spiritual dance practices. Drawing on interviews with this community, I describe the techniques of sacred and spiritual belly dancers, how these dancers theorize performance, and how the conflicts inherent to patriarchal mind-body dualism are resolved in these practices. My purpose here is twofold: to document an emergent dance tradition and to analyze its meanings in the relevant social context.